Música y Periodismo: Guía Interpretativa Para La Cobertura Periodística Musical en la Era Post Pandemia (2021 – junio 2022). - Vinueza Lema, Alexis Javier (2024)
ABSTRACT: The main objective of this research was to take a comprehensive look at the journalistic treatment of music in Ecuador, covering the period between 2021 and June 2022, with meticulous attention to both traditional and emerging media. The primary purpose of this research is to unravel and understand in depth how music-related issues are represented in national journalism, and, more specifically, to identify and evaluate the current state of music journalism in Ecuador. Throughout this research, a comprehensive exploration of the historical context that has shaped music journalism in Ecuador is undertaken, shedding light on its impact as an essential component of the country's cultural journalistic landscape. A thorough analysis of the evolution of music coverage in the media is pursued, highlighting its relevance as a journalistic product that reflects and shapes cultural perceptions in society. The research approach is based on an analytical method in which rigorousness is the backbone of the study. This approach is materialized through content analysis of a wide range of journalistic publications and interviews with experts in the field of music journalism in Ecuador. These interviews not only enrich the understanding of the dynamics of music journalism but also provide valuable insights into the trends, challenges, and opportunities facing this evolving field. The findings obtained through this analysis contribute significantly to the creation of a detailed guide to music journalism coverage in Ecuador. This guide not only addresses issues related to traditional media but also focuses specifically on emerging media, recognizing their growing influence on the dissemination of music information. Furthermore, concrete and practical recommendations are made to enhance the quality and depth of music journalism in the country, considering the particularities and challenges of the Ecuadorian context.